Sigma subunit of Escherichia coli RNA polymerase affects the function of lambda N gene. - Nakamura, Y (1979)
A new class of Escherichia coli mutants, referred to as grn, has been isolated by localized mutagenesis. These mutations affect the sigma subunit of DNA-dependent RNA polymerase (ribonucleoside 5'-triphosphate:RNA nucleotidyltransferase, EC 2.7.7.6) by abolishing the expression of the lambda N gene, and they are closely lniked to dnaG in the order dnaG-grn-uxaA. Detailed study of one such mutant, grn1, yielded the following results: (i) grn1 is a single mutation and the mutant cell shows cold-sensitivity in growth; (ii) the Grn phenotype of the mutant can easily be suppressed by secondary mutations in the beta subunit gene of RNA polymerase; (iii) purified holoenzyme of RNA polymerase isolated from the mutant showed an altered salt-dependency in vitro, and the mixed reconstitution of the mutant with the wild-type subunits showed that the sigma subunit of the grn1 mutant is altered; (iv) lambda phage mutants (lambda grg), which overcome the grn mutation, can be classified into two groups, the "nin-deletion" and the "N-mutant" groups (both of these are also able to grow on the previously described groN mutant of Georgopoulos and nusAB of Friedman); (iv) the mutant polymerase transcribed 12S as well as 7S RNA from lambda DNA in the presence of the rho factor in vitro. These results indicate that the grn mutation alters the sigma subunit of RNA polymerase and that the sigma subunit participates in activating the N-mediated antitermination mode of lambda phage transcription.